The taxable investor's manifesto : wealth management strategies to last a lifetime - Lucas, Stuart E. (John Wiley & Sons, Inc., 2020)
"It's unusual to have an author in finance who manages his own capital in the same way he advises others. Stuart Lucas is a rare breed who has been practicing what he preaches for two decades. The high value advice in this The Taxable Investor's Manifeto (TIM) should be of interest to young earners who are generating positive net cash flow, mid-career managers, business owners, business executives, all the way to family office executives for families with multi-generational wealth. Given the emphasis on taxable financial assets the market is predominantly US-oriented, though the principles discussed apply to many tax jurisdictions. In addition to serving taxable investors, TIM creates a path forward for financial advisors who are struggling to rethink their client value proposition. They have found that "beating the market" or "access to alternatives" may justify their fees in the short run but are not viable foundations for long term relationships. Indexing may be solid advice but it's hard to justify the same fees. This approach is better for clients, but it is also can guide advisors out of this bind. This personal finance book is written in a style that is accessible and engaging to anybody with interest and modest familiarity with personal finance. Using extensive footnoting, there are pathways to deeper research for those readers who are interested or who want to confirm the citations' relevance and rigor. The advice is action oriented and implementable"--